Fenomena Gay dan Lesbian Di Kota Padangsidimpuan - Amran, S.Ag., M.Si, Ali (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2020)
Abstract                Social reality shows that the existence of real gays and lesbians in the City of Padangsidimpuan, they have a poor understanding of religion, separating the purpose of life with religion, secular and hedonist. They do not live according to religious norms and state rules. So that the behavior of those who commit sexual deviation, has a fairly high selfish nature, has ruled out religious rules and norms and they are very difficult to accept advice from others. They also assume that lesbians and gays are not a social pathology, because they do not interfere with social life and are a disposition from Allah SWT that must be accepted sincerely. The background of lesbians and gays in Padangsidimpuan comes from religious-based school graduates, such as madrasas aliyah and pesantren. However, their decision to become lesbian and gay offenders is due to the comfort they get from each other. So that the religious sciences that have been studied are not used as a guide in life. In addition, they want to live with social identity and legality as lesbian and gay. Keywords: Gay and Lesbian